A Distributed Transactive Energy Mechanism for Integrating PV and Storage Prosumers in Market Operation. (May 2022) - Hou, Peng; Yang, Guangya; Hu, Junjie; Douglass, Philip J.; Xue, Yusheng
Abstract: The decreasing cost of solar photovoltaics (PVs) and battery storage systems is driving their adoption in the residential distribution system, where more consumers are becoming prosumers. Accompanying this trend is the potential roll-out of home energy management systems (HEMSs), which provide a means for prosumers to respond to externalities such as energy price, weather, and energy demands. However, the economic operation of prosumers can affect grid security, especially when energy prices are extremely low or high. Therefore, it is paramount to design a framework that can accommodate the interests of the key stakeholders in distribution systems—namely, the network operator, prosumer, and aggregator. In this paper, a novel transactive energy (TE)-based operational framework is proposed. Under this framework, aggregators interact with the distribution grid operator through a negotiation process to ensure network security, while at the lower level, prosumers submit their schedule to the aggregator through the HEMS. If network security is at risk, aggregators will send an additional price component representing the cost of security (CoS) to the prosumer to stimulate further response. The simulation results show that the proposed framework can effectively ensure the economic operation of aggregators and prosumers in distribution systems while maintaining grid security.